876Association of blood markers of inflammation, vitamin status and the kynurenine pathway with age and all-cause mortality. (2nd September 2021) - Dugué, Pierre-antoine; Hodge, Allison; Ueland, Per; Midttun, Øivind; Ulvik, Arve; Rinaldi, Sabina; MacInnis, Robert; Li, Sherly; Meyer, Klaus; Navionis, Anne-Sophie; Flicker, Leon; Severi, Gianluca; et al.
Abstract: Background: Inflammation is a key feature of aging and a cause of numerous diseases. We investigated the association of 35 blood markers involved in inflammatory processes with age and mortality and developed a signature of 'inflammaging'. Methods: Thirty-five blood markers relating to the kynurenine pathway, vitamin status, and inflammation were measured in 976 participants in the Melbourne Collaborative Cohort Study at baseline (1990-1994, median age 59 years) and follow-up (2003-2007, median age 70 years). Associations of each marker with age and all-cause mortality were assessed using linear and Cox regression, respectively. A signature of inflammaging was obtained via Lasso regression of age on the markers and tested for association with mortality; we compared mortality associations for this signature and two weighted scores across all markers associated with age and mortality, respectively. Results: Most markers (29/35) were associated with age, with strongest associations observed for cystatin C, neopterin, quinolinic acid, and the kynurenine/tryptophan ratio, PAr index, and 3-hydroxykynurenine/xanthurenic acid ratio. Many markers (14/35) showed strong associations with mortality in particular neopterin, quinolinic acid, HK/XA, PAr index, CRP, IL-6 and KTr. The inflammaging signature included six markers and showed strong association with mortality (HR = 1.5, 95%CI: 1.3-1.7), almost as strong as the association of weighted scores combining all measured markers. Conclusions: Our study highlights the key role played by markers of the kynurenine pathway and vitamin B6 catabolism in aging, along with other well-established inflammation-related markers. Key messages: A signature of 'inflammaging' based on 6 markers may be useful to better predict mortality.